Just enough AutoCAD 2007 - Omura, George (Wiley, 2006)
In this newest edition of his indispensable book, bestselling AutoCAD author and expert George Omura offers a practical and comprehensive guide to help you easily and efficiently learn the basics of AutoCAD. His straightforward explanations and task-based approach--thoroughly updated for AutoCAD 2007 and AutoCAD LT 2007--make this practical book more valuable than ever.